In defense of lightweight rowing - Giesbrecht, J. (Sport, Ethics and Philosophy, 2022)
This paper offers a defense of weight categories in rowing. Lightweight rowing—the most commonly used term for the weight category in rowing`s often bifurcated categorisation system—is under credible threat of being eliminated at virtually all levels of rowing in Canada and the U.S. (Giesbrecht 2020; Moran 2018; Usrowing n.d.). The health concerns associated with weight loss reflect the most problematic aspects of lightweight rowing, where the acceptable limits of harm that one must tolerate in sport are brought into question. Additionally, for lightweights who are nearly as competitive as their openweight counterparts, such category protection may be unnecessary. These concerns prompt reflection on the purpose and policies behind these categories. The impetus for this paper accordingly stems from the lack of detailed explanation for this kind of categorisation. Justification for weight categories is scant or has simply been assumed as legitimate within the status quo and so, in the absence of any constructive debate on the topic, I will attempt to articulate the neglected rationale for why lightweight rowing ought to exist. In doing so, suggestions for further rules and policy improvements to lightweight rowing will be identified.